Androgen receptor CAG repeat polymorphism and hypothalamic‐pituitary‐gonadal function in Filipino young adult males. Issue 1 (15th July 2016) - Ryan, Calen P.; McDade, Thomas W.; Gettler, Lee T.; Eisenberg, Dan T. A.; Rzhetskaya, Margarita; Hayes, M. Geoffey; Kuzawa, Christopher W.
Abstract: Objectives: Testosterone (T), the primary androgenic hormone in males, is stimulated through pulsatile secretion of LH and regulated through negative feedback inhibition at the hypothalamus and pituitary. The hypothalamic‐pituitary‐gonadal (HPG) axis also controls sperm production through the secretion of follicle‐stimulating hormone (FSH). Negative feedback in the HPG axis is achieved in part through the binding of T to the androgen receptor (AR), which contains a highly variable trinucleotide repeat polymorphism (AR‐CAGn). The number of repeats in the AR‐CAGn inversely correlates with transcriptional activity of the AR. Thus, we predicted longer AR‐CAGn to be associated with higher T, LH, and FSH levels. Methods: We examined the relationship between AR‐CAGn and total plasma T, LH, and FSH, as well as "bioavailable" morning (AM‐T) and evening (PM‐T) testosterone in 722 young (21.5 ± 0.5 years) Filipino males. Results: There was no relationship between AR‐CAGn and total T, AM‐T, or LH ( P > .25 for all). We did observe a marginally non‐significant ( P = .066) correlation between AR‐CAGn and PM‐T in the predicted direction, and a negative correlation between AR‐CAGn and FSH ( P = .005). Conclusions: Our results both support and differ from previous findings in this area, and study parameters that differ between our study and others, such as participant age, sample time, and the role of other hormones should be considered when interpreting our findings. While our data point to a modest effect of AR‐CAGn on HPG regulation at best, the AR‐CAGn may still affect somatic traits by regulating androgenic activity at peripheral tissues.